Tinjauan Faktor Keamanan dan Kenyamanan di Sudirman Walk Palembang - Sary, Reny Kartika; Jaya, Meldo Andi; Rizal, Randy (Universitas muhammadiyah palembang, 2023)
A great pedestrian facility is one that could satisfy everyone's desire for walking by giving them a sense of security and comfort. A good sidewalk could encourage a sustainable environment and needs to conform to the requirements for size and supporting infrastructure. Similar to Palembang City, the sidewalk is located alongside Sudirman Walk can be considered as a pilot project since it already satisfies requirements for size, material use, and amenities that promote pedestrian safety and comfort. The aim of this research is to review the pedestrian amenities Sudirman Walk using qualitative descriptive methods through field observations, literature reviews, and comparisons. The Boston Transportation Department and The KEMENPUPR constitute the framework for the indicators used to evaluate the sidewalk's comfort and safety aspects. According to the the results, the sidewalk along the Sudirman road already has a feature that can help pedestrians feel safe and at comfort, especially considering the flow of traffic. However, due to its material use, this walkway is not completely safe for pedestrians, as it still has a risk to cause slips.